Economy of the Erivan region and the Role of the Development of the Transport System in its Transformation in the Middle of the XIX - Early XX Century - I. F. Kazimbeyli (Научный диалог)
The development of the transport and communication system of the Erivan region in the middle of the XIX - early XX centuries, as well as the impact it had on the economic life of the region in the specified period is considered. Analyzing the development of industry in the Erivan Oblast in the late XIX - early XX centuries, it was noted that neither foreign nor Russian capital was involved in the industry of the studied region until the end of the XIX century. This is the novelty and relevance of the study. The main attention is paid to the fact that until the end of the XIX century the industry of the region was limited to two main areas: the processing of copper and the production of wine and brandy. It is emphasized that the development of the transport system in the South Caucasus led to radical changes in many areas of industry, including trade. Based on the analysis of historical sources, it is proved that since the beginning of the 20th century, the role of Russian capital has increased in the industry of the Erivan region, without a doubt. It is shown that the industry of the region developed not due to consolidation and concentration, but due to expansion of the initial enterprises.